Hydrogenation catalyst for producing low-sulfur ship fuel as well as preparation method and application of hydrogenation catalyst
Through the catalyst preparation method of gallium-modified silicon-aluminum support and active metal components, the problems of low-sulfur ship combustion production difficulties and insufficient catalyst activity in the prior art are solved, and efficient and economical low-sulfur ship combustion production are achieved.
Patent Information
- Application Number
- CN202311317078.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-12
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-10-12
AI Technical Summary
The existing technology is difficult to effectively produce low-sulfur shipbuilding, and the activity and stability of the existing catalysts are insufficient, which cannot meet the requirements of the IMO 2020 sulfur limit policy.
The catalyst is prepared by using gallium-modified silicon-aluminum support and active metal components. Through specific preparation methods and composition optimization, the active metal utilization, wear resistance and hydrogenation properties of the catalyst are improved.
The catalyst has achieved high selective desulfurization activity and low aromatic saturation activity, and is suitable for low sulfur ship combustion production of heavy and inferior residual oil, reducing hydrogen consumption and production costs.
Smart Images

Figure BDA0004489676280000091 
Figure BDA0004489676280000101 
Figure BDA0004489676280000102
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalyst preparation, and relates to a catalytic material and a preparation method thereof, and specifically relates to a hydrogenation catalyst for producing low-sulfur marine fuel, and a preparation method and application thereof. Background Art
[0002] As global environmental problems continue to intensify, countries around the world have successively introduced environmental regulations to limit the sulfur content of marine fuel oil (hereinafter referred to as marine fuel). The International Maritime Organization requires that the upper limit of sulfur content in marine fuel oil be reduced to 0.5wt% on January 1, 2020. After the implementation of the IMO 2020 sulfur limit policy, it is expected that low-sulfur heavy marine fuel oil will account for about 45% of the total consumption in the short term and about 40% in the long term. The production of low-sulfur marine fuel oil is in short supply.
[0003] At present, high-sulfur heavy marine fuel is mainly produced by blending. The blending components are mainly derived from high-sulfur residual oil that is difficult to handle in refineries, as well as non-ideal by-products such as catalytic oil slurry and low-quality secondary processed distillate oil. The focus of blending is to ensure that the viscosity, stability, and the content of metal aluminum and silicon (catalyst powder in catalytic oil slurry) meet the quality requirements. However, it is difficult to directly produce residual low-sulfur marine fuel with a sulfur content of less than 0.5wt% using the current blending components. Low-sulfur residual oil must be added for blending. Similarly, if a large amount of high-priced low-sulfur straight-run residual oil is used to blend and produce heavy marine fuel, the production cost of heavy marine fuel will be greatly increased. Targeted development of residual oil hydrogenation catalysts with high desulfurization performance is an effective means to economically produce low-sulfur marine fuel.
[0004] CN1458236A discloses a method for preparing a heavy oil hydrodemetallization and desulfurization catalyst. The catalyst preparation method uses two different forms of aluminum-containing materials, one is calcined aluminum oxide, and the other is aluminum hydroxide dry rubber powder, with alkali metal and / or alkaline earth metal elements as additives, the additives are partially premixed with the aluminum hydroxide dry rubber powder, and partially loaded on the catalyst by impregnation, so that the additives are unevenly distributed on the catalyst. The catalyst obtained by this method is not very suitable for the production of low-sulfur marine fuel, and its activity and stability need to be further improved.
[0005] CN114749193A discloses a hydrogenation catalyst for producing low-sulfur marine fuel and its preparation method. The catalyst comprises a silicon-aluminum material and a first metal and a second metal supported on the silicon-aluminum material; wherein the first metal is selected from at least one of Group IVB metals, Group VIB metals, and Group VIII metals; the second metal is selected from at least one of Group VIB metals and Group VIII metals. The preparation method comprises: adding an acidic aluminum source to a silicon source, and then mixing it with a first metal salt solution to obtain a mixed solution A; contacting the mixed solution A with an alkaline aluminum source in the presence of water to obtain a slurry B; subjecting the slurry B to a hydrothermal treatment to obtain a carrier precursor; uniformly mixing the carrier precursor, a molding agent, and an adhesive, and then molding, drying, and calcining to obtain a carrier; mixing the carrier with a second metal salt solution, and further drying and calcining to obtain a catalyst. The acidity of the catalyst is too strong, with the ratio of B acid to L acid reaching 0.3 to 0.8. While achieving desulfurization, this method often also causes cracking reactions of hydrocarbons, which not only increases processing costs but also greatly affects the properties of marine fuel. Summary of the invention
[0006] In view of the problems existing in the prior art, the present invention aims to provide a hydrogenation catalyst for producing low-sulfur marine fuel and its preparation method and application. The catalyst of the present invention has the advantages of high utilization rate of active metals, good wear resistance, high hydrogenation performance, especially high selective desulfurization activity, and low aromatic saturation activity, and is suitable for use in the process of producing low-sulfur marine fuel from heavy and inferior residual oil.
[0007] The first aspect of the present invention provides a hydrogenation catalyst for producing low-sulfur marine fuel, comprising a gallium-modified silica-alumina carrier and an active metal component. The gallium-modified silica-alumina carrier has a mass content of gallium oxide of 2.0% to 5.0%, a mass content of silicon dioxide of 20.0% to 60.0%, and a mass content of aluminum oxide of 35.0% to 78.0%, based on the mass of the gallium-modified silica-alumina carrier.
[0008] According to the present invention, the active metal comprises at least one metal component selected from Group VIII and at least one metal component selected from Group VIB; the Group VIII metal is preferably nickel and / or cobalt, and the Group VIB metal is preferably molybdenum and / or tungsten.
[0009] According to the present invention, based on the mass of the catalyst, the mass content of the carrier is 74.0% to 87.0%, the content of Group VIII in terms of oxide is 2.0% to 6.0%, and the content of Group VIB metal in terms of oxide is 10.0% to 20.0%.
[0010] According to the present invention, the catalyst also contains phosphorus, and the content of phosphorus is 1.0% to 5.0% based on the mass of the catalyst and calculated as phosphorus pentoxide.
[0011] According to the present invention, the properties of the catalyst are as follows: the specific surface area is 180 to 230 m 2 / g, the pore volume is 0.5-0.7mL / g, the average pore diameter is 10.0-30.0nm, and the mechanical strength is 120-190N / cm.
[0012] According to the present invention, the total acid content of the catalyst is 0.23-0.57 mmol / g, the B acid content is 0.03-0.07 mmol / g, and the L acid content is 0.2-0.5 mmol / g.
[0013] The second aspect of the present invention provides a method for preparing the above-mentioned hydrogenation catalyst for producing low-sulfur marine fuel, comprising:
[0014] (1) mixing an acidic aluminum salt aqueous solution, a silicon source, and an organic acid, stirring and mixing to obtain a material I;
[0015] (2) subjecting material I to a gallium-containing solution and an alkaline aluminum salt aqueous solution in parallel for precipitation reaction to obtain material II;
[0016] (3) subjecting material II and a nonionic surfactant to hydrothermal treatment to obtain a gallium-modified silicon-aluminum material;
[0017] (4) kneading the gallium-modified silicon-aluminum material obtained in step (3), an adhesive, an extrusion aid and water, drying and calcining to obtain a catalyst carrier;
[0018] (5) Loading the active metal component onto the catalyst carrier obtained in step (4), drying and calcining to obtain the catalyst.
[0019] According to the present invention, the acidic aluminum salt in step (1) is at least one of aluminum sulfate, aluminum chloride or aluminum nitrate, and the acidic aluminum salt solution is Al 2 O 3 The concentration of the silicon source is 20-100 g / 100 mL; the silicon source is one or more of water-soluble silicate, water glass, and silica sol, and the silicon source is SiO 2 The concentration of the silicon source (in the form of SiO 2 ) and the acidic aluminum source (in terms of Al 2 O 3 The weight ratio of the above-mentioned components is 1:1 to 7:1.
[0020] According to the present invention, the organic acid in step (1) is one or more of maleic acid, fumaric acid, adipic acid, tartaric acid, citric acid, oxalic acid, acetic acid, salicylic acid, and malic acid. The mass concentration of the organic acid is 7% to 16%. The amount of the organic acid added is such that the pH value of the material I is 2 to 4, preferably 3 to 4.
[0021] According to the present invention, the gallium-containing solution in step (2) is a gallium nitrate solution, and the concentration of the gallium-containing solution is 0.5 to 2.5 mol / L. The alkaline aluminum salt is at least one of sodium aluminate or potassium aluminate. 2 O 3 The concentration of the gallium-containing solution is 20 to 100 g / 100 mL. The ratio of the parallel flow rates of the gallium-containing solution, the material I, and the alkaline aluminum salt solution is 1:3 to 7:1 to 3. The reaction temperature of step (2) is 60 to 90°C, the reaction time is 60 to 180 minutes, and the pH value is 8.0 to 9.7. The reaction is preferably carried out under stirring conditions, and the stirring rate is 100 to 500 rad / min, preferably 150 to 450 rad / min.
[0022] According to the present invention, the nonionic surfactant in step (3) is selected from one or more of polyethylene glycol, alkyl alcohol amide, and polyether; the alkyl alcohol amide is one or more of lauryl diethanolamine and coconut oil fatty acid diethanolamide; the polyether is one or more of AEO-6 and AEO-9; the molecular weight of the polyethylene glycol is 200-1000, preferably 200-700; the amount of the nonionic surfactant added is 0.1%-5% of the mass of the material II obtained in step (2) in terms of alumina, preferably 0.5%-3%. The concentration of the nonionic surfactant is 30-70g / 100mL.
[0023] According to the present invention, the conditions of the sealed hydrothermal treatment described in step (3) are as follows: the hydrothermal treatment temperature is 80-130°C, the time is 3-18 hours, wherein the heating rate is 8-15°C / min. Preferably, the hydrothermal treatment adopts two-stage hydrothermal treatment, the first stage hydrothermal treatment temperature is 80-110°C, the first stage hydrothermal treatment time is 1-9 hours, the second stage hydrothermal treatment temperature is 100-130°C, the second stage hydrothermal treatment time is 1-9 hours, wherein the second stage hydrothermal treatment temperature is at least 15°C higher than the first stage hydrothermal treatment temperature, preferably at least 20°C higher. Washing and drying can be carried out after the reaction. Drying conditions are: 100-170°C for 1-7h.
[0024] According to the present invention, the preparation process of the catalyst carrier described in step (4) is to add an extrusion aid, a peptizing agent, etc. to the gallium-modified silicon-aluminum material and knead it into a plastic body and then form it. The forming can adopt a conventional forming method, such as extrusion forming, tablet forming, etc., preferably extrusion forming. The amount of the extrusion aid added is 1.0wt% to 4.0wt% of the gallium-modified silicon-aluminum material; the amount of the peptizing agent added is 1.0wt% to 5.0wt% of the gallium-modified silicon-aluminum material; the amount of water added is 80.0wt% to 100.0wt% of the gallium-modified silicon-aluminum material. The extrusion aid is sesbania powder, and the peptizing agent is nitric acid.
[0025] According to the present invention, the drying temperature in step (4) is 120-160° C., the drying time is 2-6 hours, the roasting temperature is 550-800° C., and the roasting time is 4-6 hours.
[0026] According to the present invention, the method of loading the active metal component onto the catalyst support obtained in step (4) in step (5) is preferably an impregnation method. The active metal comprises at least one metal component selected from Group VIII and at least one metal component selected from Group VIB. The Group VIII metal is preferably nickel and / or cobalt, and the Group VIB metal is preferably molybdenum and / or tungsten.
[0027] According to the present invention, the impregnation in step (5) is performed by spraying, and equal volume impregnation or supersaturated impregnation is performed. Preferably, after impregnation, the sample is placed under closed conditions at 20 to 30° C. for 6 to 12 hours before the drying step is performed.
[0028] According to the present invention, the active metal in the impregnation solution used in step (5) is calculated as metal oxide, wherein the content of Group VIB metal is 150-450 g / L, preferably 300-400 g / L, and the content of Group VIII metal is 10-120 g / L, preferably 40-60 g / L. Furthermore, the impregnation solution also contains a phosphorus source; calculated as phosphorus, the concentration of phosphorus is 20-80 g / L, preferably 40-60 g / L.
[0029] According to the present invention, in step (5), the drying condition is 100-160° C. for 1-8 hours; the roasting condition is 450-650° C. for 2-7 hours, preferably 480-600° C. for 2-7 hours.
[0030] A third aspect of the present invention provides an application of the above catalyst or the catalyst obtained by the above preparation method in the production of low-sulfur marine fuel by hydrogenation of inferior residual oil.
[0031] Further, in the above application, the reaction conditions are: reaction pressure of 10-18 MPa, reaction temperature of 380-430°C, liquid hourly volume space velocity of 0.1-0.6 h -1 , the volume ratio of hydrogen to oil is 400-800.
[0032] Compared with the prior art, the present invention has the following advantages:
[0033] 1. The catalyst for producing low-sulfur marine fuel of the present invention comprises a carrier and an active metal component, wherein the carrier comprises a gallium-modified silicon-aluminum carrier; the total acid content of the catalyst is 0.23-0.57 mmol / g, the B acid content is 0.03-0.07 mmol / g, and the L acid content is 0.2-0.5 mmol / g. The catalyst of the present invention has suitable B acid and rich L acid content, has the advantages of high desulfurization rate, low aromatic saturation rate and cracking rate, is suitable for the hydrogenation conversion process of sulfide in asphaltene in the production process of low-sulfur marine fuel, has high hydrogenation desulfurization activity and good stability.
[0034] 2. In the preparation method of the gallium-modified silicon-aluminum carrier provided by the present invention, the addition of organic acid increases the absolute value of the system Zeta potential, increases the electrostatic repulsion between particles, and is beneficial to the dispersibility and fluidity of the slurry. At the same time, the acidified silica gel group is adsorbed on the aluminum hydroxide colloid, providing a crystal nucleus for subsequent reactions, promoting the increase of the prepared carrier precursor grains, and is beneficial to the formation of a large pore volume and large pore size carrier precursor coated with an organic chain. The non-ionic surfactant forms hydrogen bonds with the hydroxyl groups of the aluminum hydroxide hydrosol to avoid mutual adhesion and aggregation between particles, so that the gel particles are arranged in an orderly crystal precipitate or a colloid with a crystal structure, and the free silicon species can undergo ion exchange with the non-ionic surfactant to form a complex, and finally form a mesoporous material with a stable structure. By replacing part of the framework Al with Ga, since Ga can enter the Si-O-Al framework structure like Al, the adverse effect of the reduction of framework Al on crystallinity is avoided while adjusting the acidity, and a silicon-aluminum material with controllable acidity is obtained. At the same time, the weak acid sites formed by the framework Ga and the gallium existing outside the framework can synergize with the strong B acid sites formed by Si-O-Al, which is beneficial to selective hydrogenation and desulfurization, and reduces the saturation of aromatics to produce low-sulfur marine fuel with low hydrogen consumption and reduced costs.
[0035] 3. The catalyst of the present invention is used in the process of producing low-sulfur marine fuel from heavy low-quality residual oil, and has the advantages of high active metal utilization, good wear resistance, high hydrogenation performance, especially high selective desulfurization activity and low aromatic saturation activity. DETAILED DESCRIPTION
[0036] The technical solution of the present invention is described in detail below in conjunction with embodiments.
[0037] In the present invention, the total acid content, L acid or B acid is determined by infrared spectroscopy, and the instrument is American Nicot Fourier infrared spectrometer-6700. The determination method is as follows: weigh 20 mg of a sample with a particle size less than 200 mesh, press it into a thin slice with a diameter of 20 mm, and install it on the sample holder of the absorption cell. Put 200 mg of the sample into the instrument hanging cup, connect the absorption cell and the adsorption tube, and evacuate the vacuum to a vacuum degree of 4×10 -2Pa, the temperature was raised to 500 ° C and maintained for 1 hour to remove the adsorbent on the sample surface. After cooling to room temperature, pyridine was adsorbed to saturation, and the temperature was continued to rise to 160 ° C, balanced for 1 hour, and the physically adsorbed pyridine was desorbed to obtain the total acid content, B acid and L acid, where the acid content unit is mmol / g. In the infrared spectrum, the 1450 cm -1 The absorption peak nearby is L acid, 1540cm -1 The absorption peak nearby is B acid.
[0038] In the present invention, the specific surface area, pore volume and average pore size are measured by using an ASAP2420 fully automatic physical adsorption instrument from Micromeritics Instruments, Inc., USA. The measurement method is as follows: After the sample is treated at 300°C and 0.1 MPa for 4 h, the liquid N 2 As adsorbent, the adsorption temperature is -196℃, and the analysis test is carried out after accurate weighing. The specific surface area is calculated according to the BET method, and the pore volume and average pore diameter are calculated according to the BJH method.
[0039] In the present invention, the mechanical strength is measured by using a ZQJ-III particle strength tester produced by Dalian Intelligent Testing Machine Factory.
[0040] In the present invention, the catalyst composition is tested by spectrophotometry, and the testing instrument is a Lambda 365 ultraviolet spectrophotometer.
[0041] In the present invention, the sulfur content and nitrogen content are determined by the American PHOTONLAB sulfur and nitrogen analyzer, and the determination method is as follows: the hydrocarbon sample is directly injected into the cracking tube or the injection boat, and the sample is sent to the high-temperature combustion tube by the injector. The nitride in the sample is quantitatively converted into NO, and the reaction product is carried by the carrier gas, passes through the dryer to remove the water therein, and enters the reaction chamber. NO reacts with O from the ozone generator in the reaction chamber. 3 The gas reacts and converts into excited NO 2 When the excited NO 2 When it transitions to the ground state, it emits photons. The emitted light signal is detected by a photomultiplier tube at a specific wavelength. Its intensity is proportional to the total nitrogen content in the original sample. Therefore, the total nitrogen content in the sample can be determined by measuring the intensity of chemiluminescence. In oxygen-rich conditions, sulfur is oxidized to SO 2 ; The gas generated by the combustion of the sample is irradiated by ultraviolet light after removing water, SO 2 The energy absorbed by ultraviolet light is converted into excited SO 2 , when the excited state of SO 2 Return to steady state SO 2 When the fluorescence is emitted, it is detected by a photomultiplier tube, and the sulfur content of the sample is calculated from the obtained signal value.
[0042] In the present invention, the percentage of aromatic fraction refers to T0618 "Asphalt Chemical Component Test (Four-Component Method)" in the Ministry of Communications Standard JTJ 052-2000 "Test Procedures for Asphalt and Asphalt Mixtures for Highway Engineering" and the petrochemical industry standard NB / SH / T 0509-2010 "Method for Determination of Petroleum Asphalt Components". Column chromatography is used to first separate asphaltene with n-heptane, filter and reflux n-heptane to separate solubles mixed in the asphaltene, and then reflux toluene to dissolve and purify the asphaltene. Secondly, the deasphalted component is concentrated and adsorbed on an alumina chromatographic column, and washed with n-heptane, toluene, and toluene-ethanol in turn to obtain saturated fractions, aromatic fractions, and colloids, respectively.
[0043] In the present invention, the carbon residue % determination instrument is the BT-17144 trace carbon residue determination instrument, and the determination method is to place the weighed sample into a sample tube, and heat it to 500°C in an inert gas (nitrogen) atmosphere according to a prescribed temperature program. The volatile substances generated during the reaction are carried away by the nitrogen, and the carbonaceous residue left behind is reported as a percentage of the original sample.
[0044] In the present invention, unless otherwise specified, % refers to mass percentage.
[0045] Example 1
[0046] (1) Prepared with Al 2 O 3 Aluminum sulfate solution with a concentration of 50g / 100mL and SiO 2 The concentration is 60g / 100mL silica sol solution. Silicon source (in the form of SiO 2 ) and acidic aluminum source (in terms of Al 2 O 3 The weight ratio of the mixture is 2.4:1. Citric acid with a mass concentration of 8% is added to adjust the pH of the solution to 3 to obtain material I.
[0047] (2) 2.0 L of purified water was added to the reactor and heated to 60° C. The stirring rate was 200 rad / min. The flow rates of material I, 60 g / 100 mL of sodium aluminate solution and 2 mol / L of gallium nitrate solution were controlled to be 50 mL / min, 20 mL / min and 10 ml / min respectively, and they were continuously added to the reactor. During the reaction, the reaction pH was controlled to be 8, the reaction time was 180 min, and the reaction temperature was 60° C.
[0048] (3) After the precipitation reaction is completed, the temperature is adjusted to 95°C and the stirring rate is adjusted to 300rad / min. According to the addition amount of non-ionic surfactant being 2.4wt% of the mass of material II in terms of alumina, a 55g / 100mL polyethylene glycol (molecular weight 600) solution is introduced into the reactor for hydrothermal treatment. After sealing, the temperature is raised to 100°C at a rate of 15°C / min and kept constant for 3 hours, and then the temperature is raised to 120°C at a rate of 10°C / min and kept constant for 6 hours. The reacted slurry is washed with hot water at 90°C until neutral, and the drying condition is 120°C for 3 hours to obtain gallium-modified silicon-aluminum material.
[0049] (4) Weigh 448 g of gallium-modified silicon-aluminum material, add 12 g of sesbania powder, 9 g of nitric acid and 378 g of water, mix, knead and shape, dry at 140°C for 3 hours, and calcine at 650°C for 4 hours to obtain catalyst carrier A.
[0050] (5) 36 g of molybdenum trioxide, 9 g of basic nickel carbonate, and 16.2 g of phosphoric acid were used to prepare 90 mL of impregnation solution, which was impregnated on the carrier A-0 by spraying to obtain A-1. A-1 was placed in a closed container at 25°C for 6 hours, dried at 120°C for 4 hours, and finally calcined at 550°C for 4 hours to obtain CA-1.
[0051] Example 2
[0052] (1) Prepared with Al 2 O 3 Aluminum sulfate solution with a concentration of 30g / 100mL and SiO 2 The concentration is 60g / 100mL silica sol solution. Silicon source (in the form of SiO 2 ) and acidic aluminum source (in terms of Al 2 O 3 The weight ratio of the raw materials to the raw materials is 4:1. Citric acid with a mass concentration of 10% is added to adjust the pH of the solution to 4 to obtain material I.
[0053] (2) 2.0 L of purified water was added to the reactor and heated to 80° C. The stirring rate was 250 rad / min. The flow rates of material I, 80 g / 100 mL of sodium aluminate solution and 2.5 mol / L of gallium nitrate solution were controlled to be 60 mL / min, 11 mL / min and 10 ml / min respectively, and they were continuously added to the reactor. During the reaction, the reaction pH was controlled to be 8.5, the reaction time was 90 min, and the reaction temperature was 80° C.
[0054] (3) After the precipitation reaction is completed, the temperature is adjusted to 85°C and the stirring rate is adjusted to 350rad / min. According to the amount of non-ionic surfactant added, which is 2.4wt% of the mass of material II based on alumina, a 60g / 100mL lauryl diethanolamine solution is introduced into the reactor for hydrothermal treatment. After sealing, the temperature is increased to 90°C at a rate of 10°C / min and kept constant for 4 hours, and then the temperature is increased to 130°C at a rate of 15°C / min and kept constant for 4 hours. The reacted slurry is washed with hot water at 90°C until neutral, and the drying condition is 130°C for 4 hours to obtain gallium-modified silicon-aluminum material.
[0055] (4) Weigh 435 g of gallium-modified silicon-aluminum material, add 12 g of sesbania powder, 11.2 g of nitric acid and 375 g of water, mix, knead and shape, dry at 120° C. for 4 hours, and calcine at 620° C. for 6 hours to obtain catalyst carrier B.
[0056] (5) 32 g of molybdenum trioxide, 7.8 g of basic nickel carbonate, and 14.2 g of phosphoric acid were used to prepare 90 mL of impregnation solution, which was impregnated on the carrier B-0 by spraying to obtain B-1. B-1 was placed in a closed container at 24°C for 6 hours, dried at 120°C for 4 hours, and finally calcined at 500°C for 6 hours to obtain CB-1.
[0057] Example 3
[0058] (1) Prepared with Al 2 O 3 Aluminum sulfate solution with a concentration of 80g / 100mL and SiO 2 The concentration of silica sol solution is 40g / 100mL. 2 ) and acidic aluminum source (in terms of Al 2 O 3 The weight ratio of the raw materials is 1:1. Citric acid with a mass concentration of 15% is added to adjust the pH of the solution to 3 to obtain material I.
[0059] (2) 2.0 L of purified water was added to the reactor and heated to 80° C. The stirring rate was 200 rad / min. The flow rates of material I, 75 g / 100 mL sodium aluminate solution and 2 mol / L gallium nitrate solution were controlled to be 30 mL / min, 15 mL / min and 10 ml / min respectively, and they were continuously added to the reactor. During the reaction, the reaction pH was controlled to be 9, the reaction time was 120 min, and the reaction temperature was 80° C.
[0060] (3) After the precipitation reaction is completed, the temperature is adjusted to 95°C and the stirring rate is adjusted to 400rad / min. According to the amount of non-ionic surfactant added, which is 2.6wt% of the mass of material II in terms of alumina, a 45g / 100mL AEO-9 solution is introduced into the reactor for hydrothermal treatment. After sealing, the temperature is increased to 100°C at a rate of 15°C / min and kept constant for 8 hours, and then the temperature is increased to 130°C at a rate of 10°C / min and kept constant for 8 hours. The reacted slurry is washed with hot water at 90°C until neutral, and the drying condition is 120°C for 4 hours to obtain gallium-modified silicon-aluminum material.
[0061] (4) Weigh 446 g of gallium-modified silicon-aluminum material, add 15 g of sesbania powder, 9 g of nitric acid and 363 g of water, mix, knead and shape, dry at 120° C. for 5 hours, and calcine at 750° C. for 5 hours to obtain catalyst carrier C.
[0062] (5) 36 g of molybdenum trioxide, 9 g of basic nickel carbonate, and 16.2 g of phosphoric acid were used to prepare 90 mL of impregnation solution, which was impregnated on the carrier C-0 by spraying to obtain C-1. C-1 was placed in a closed container at 26°C for 6 hours, dried at 120°C for 4 hours, and finally calcined at 500°C for 6 hours to obtain CC-1.
[0063] Example 4
[0064] (1) Prepared with Al 2 O 3 Aluminum sulfate solution with a concentration of 65g / 100mL and SiO 2 The concentration is 70g / 100mL silica sol solution. Silicon source (in the form of SiO 2 ) and acidic aluminum source (in terms of Al 2 O 3 The weight ratio of the raw materials is 2:1. Citric acid with a mass concentration of 15% is added to adjust the pH of the solution to 3 to obtain material I.
[0065] (2) 2.0 L of purified water was added to the reactor and heated to 70° C. The stirring rate was 300 rad / min. The flow rates of material I, 90 g / 100 mL sodium aluminate solution and 1.0 mol / L gallium nitrate solution were controlled to be 60 mL / min, 25 mL / min and 10 ml / min respectively, and they were continuously added to the reactor. During the reaction, the reaction pH was controlled to be 9, the reaction time was 150 min, and the reaction temperature was 70° C.
[0066] (3) After the precipitation reaction is completed, the temperature is adjusted to 95°C and the stirring rate is adjusted to 350rad / min. According to the addition amount of non-ionic surfactant being 2.5wt% of the mass of material II in terms of alumina, a 60g / 100mL polyethylene glycol (molecular weight 400) solution is introduced into the reactor for hydrothermal treatment. After sealing, the temperature is raised to 100°C at a rate of 12°C / min and kept constant for 4 hours, then the temperature is raised to 130°C at a rate of 15°C / min and kept constant for 8 hours. The reacted slurry is washed with hot water at 90°C until neutral, and the drying condition is 140°C for 5 hours to obtain gallium-modified silicon-aluminum material.
[0067] (4) Weigh 435 g of gallium-modified silicon-aluminum material, add 12 g of sesbania powder, 11 g of nitric acid and 375 g of water, mix, knead and shape, dry at 130° C. for 5 hours, and calcine at 750° C. for 8 hours to obtain catalyst carrier D.
[0068] (5) 36 g of molybdenum trioxide, 7.6 g of basic nickel carbonate, and 17.7 g of phosphoric acid were used to prepare 90 mL of impregnation solution, which was impregnated on the carrier D-0 by spraying to obtain D-1. D-1 was placed in a closed container at 25°C for 6 hours, dried at 120°C for 4 hours, and finally calcined at 480°C for 6 hours to obtain CD-1.
[0069] Comparative Example 1
[0070] Compared with Example 1, the difference is that no organic acid is added in step (1) to adjust the pH value, and the rest is the same as Example 1.
[0071] A comparative hydrogenation catalyst DCA-1 was prepared.
[0072] Comparative Example 2
[0073] Compared with Example 1, the difference is that no nonionic surfactant is added in step (3), and material II is subjected to hydrothermal treatment alone. The rest is the same as Example 1.
[0074] A comparative hydrogenation catalyst DCA-2 was prepared.
[0075] Comparative Example 3
[0076] Compared with Example 1, the difference is that no gallium nitrate solution is added in step (2).
[0077] A comparative hydrogenation catalyst DCA-3 was prepared.
[0078] Comparative Example 4
[0079] The feed is the same as that in Example 1, but without adding the gallium nitrate solution. Compared with Example 1, the difference is that the catalyst preparation method of this example is processed according to the following steps, and the rest is the same as Example 1. The steps are:
[0080] (1) adding an acidic aluminum source aluminum sulfate solution to a silicon source silica sol, and then mixing it with a first metal salt nickel salt solution, and adjusting the solution pH to 3 to obtain a mixed solution A;
[0081] (2) co-precipitating the mixed solution A with sodium aluminate (alkaline aluminum source) in the presence of water to obtain slurry B;
[0082] (3) The slurry B is subjected to hydrothermal treatment to obtain a carrier precursor; wherein the treatment temperature is 220° C., the treatment pressure is 0.3 MPa, and the treatment is carried out for 2 hours.
[0083] (4) the carrier precursor, the forming agent and the adhesive obtained in step (3) are mixed evenly, molded, dried at 120° C. for 6 h, and calcined at 650° C. for 3 h to obtain a carrier;
[0084] (5) The support was mixed with a second metal salt solution (containing molybdenum trioxide, basic nickel carbonate, and phosphoric acid), and the mixture was further dried and calcined at 550° C. for 4 h to obtain a catalyst. A comparative hydrogenation catalyst DCA-4 was obtained.
[0085] Table 1 Composition of the catalyst obtained in each example
[0086] project Example 1 Example 2 Example 3 Example 4 Catalyst composition <![CDATA[MoO 3 ,wt%]]> 12.9 12.5 12.6 12.8 NiO, wt% 4.8 5.0 4.6 4.7 <![CDATA[P 2 O 5 ,wt%]]> 3.2 2.5 2.7 2.5 Carrier, wt% 79.1 80.0 80.1 80.0 Carrier composition <![CDATA[Al 2 O 3 ,wt%]]> 64.9 64.1 64.8 65.2 <![CDATA[SiO 2 ,wt%]]> 32.7 33.2 32.9 32.6 <![CDATA[Ga 2 O 3 ,wt%]]> 2.4 2.7 2.3 2.2 nature <![CDATA[Specific surface area, m 2 / g]]> 198 205 211 202 <![CDATA[Pore volume, cm 3 / g]]> 0.56 0.54 0.57 0.55 Average pore size, nm 16.8 16.5 16.7 16.3 Mechanical strength, N / cm 147 154 167 149
[0087] Table 1
[0088]
[0089]
[0090] Table 2 Infrared acid properties of catalysts in various embodiments and comparative examples
[0091]
[0092] Catalyst evaluation
[0093] The catalysts obtained in the examples and comparative examples were evaluated using the feedstock oils listed in Table 3. The reaction conditions were shown in Table 3. The oil produced after 1000 h of operation was sampled and analyzed. The evaluation results are shown in Table 4.
[0094] Table 3 Raw oil properties and reaction conditions
[0095]
[0096]
[0097] Table 4 Catalyst evaluation results in various examples and comparative examples
[0098]
[0099] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A hydrogenation catalyst for producing low-sulfur marine fuel, characterized in that: The catalyst comprises a gallium-modified silicon-aluminum carrier and an active metal component. The gallium-modified silicon-aluminum carrier has a mass content of gallium oxide of 2.0% to 5.0%, a mass content of silicon dioxide of 20.0% to 60.0%, and a mass content of aluminum oxide of 35.0% to 78.0%, based on the mass of the gallium-modified silicon-aluminum carrier. The total acid content of the catalyst is 0.23-0.57 mmol / g, the B acid content is 0.03-0.07 mmol / g, and the L acid content is 0.2-0.5 mmol / g.
2. The catalyst according to claim 1, characterized in that Based on the mass of the catalyst, the mass content of the carrier is 74% to 87%, the content of Group VIII in terms of oxide is 2% to 6%, and the content of Group VIB metal in terms of oxide is 10% to 20%.
3. The catalyst according to claim 1, characterized in that The properties of the catalyst are as follows: specific surface area of 180 to 230 m 2 / g, the pore volume is 0.5~0.7mL / g, and the average pore diameter is 10.0~30.0nm.
4. The catalyst according to claim 1, characterized in that The active metal comprises at least one metal component selected from Group VIII and at least one metal component selected from Group VIB; further, the Group VIII metal is preferably nickel and / or cobalt, and the Group VIB metal is preferably molybdenum and / or tungsten.
5. A method for preparing the catalyst according to any one of claims 1 to 4, comprising: (1) mixing an acidic aluminum salt aqueous solution, a silicon source, and an organic acid, stirring and mixing to obtain a material I; (2) subjecting material I to a gallium-containing solution and an alkaline aluminum salt aqueous solution in parallel for precipitation reaction to obtain material II; (3) subjecting material II and a nonionic surfactant to hydrothermal treatment to obtain a gallium-modified silicon-aluminum material; (4) kneading the gallium-modified silicon-aluminum material obtained in step (3), an adhesive, an extrusion aid and water, drying and calcining to obtain a catalyst carrier; (5) Loading the active metal component onto the catalyst carrier obtained in step (4), drying and calcining to obtain the catalyst.
6. The preparation method according to claim 5, characterized in that: The organic acid in step (1) is one or more of maleic acid, fumaric acid, adipic acid, tartaric acid, citric acid, oxalic acid, acetic acid, salicylic acid, and malic acid; And / or, the mass concentration of the organic acid is 7% to 16%; And / or, the amount of organic acid added is such that the pH value of the material I is 2-4, preferably 3-4.
7. The preparation method according to claim 5, characterized in that: The gallium-containing solution in step (2) is a gallium nitrate solution, and the concentration of the gallium-containing solution is 0.5 to 2.5 mol / L; and / or, the concentration of the alkaline aluminum salt solution in terms of Al2O3 is 20 to 100 g / 100 mL; And / or, the ratio of the parallel flow rates of the gallium-containing solution, the material I, and the alkaline aluminum salt solution is 1:3-7:1-3.
8. The preparation method according to claim 5 or 7, characterized in that: The reaction temperature of step (2) is 60-90° C., the reaction time is 60-180 minutes, and the pH value is 8.0-9.
7.
9. The preparation method according to claim 5, characterized in that: The nonionic surfactant in step (3) is selected from one or more of polyethylene glycol, alkyl alcohol amide, and polyether; And / or, the amount of the nonionic surfactant added is 0.1% to 5% by mass of the material II obtained in step (2) calculated as alumina, preferably 0.5% to 3%.
10. The preparation method according to claim 5, characterized in that: The conditions of the sealing hydrothermal treatment described in step (3) are as follows: the hydrothermal treatment temperature is 80 to 130° C. and the time is 3 to 18 hours.
11. The preparation method according to claim 5, characterized in that: The active metal in the impregnation solution used in step (5) is calculated as metal oxide, wherein the content of Group VIB metal is 150-450 g / L, preferably 300-400 g / L, and the content of Group VIII metal is 10-120 g / L, preferably 40-60 g / L; further, the impregnation solution also contains a phosphorus source; the concentration of phosphorus is 20-80 g / L, preferably 40-60 g / L.
12. Use of the catalyst according to any one of claims 1 to 4 or the catalyst obtained by the preparation method according to any one of claims 5 to 11 in the production of low-sulfur marine fuel by hydrogenation of inferior residual oil.
13. The use according to claim 12, characterized in that: The reaction conditions are: reaction pressure of 10-18 MPa, reaction temperature of 380-430°C, liquid hourly volume space velocity of 0.1-0.6 h -1 , the volume ratio of hydrogen to oil is 400-800.
Citation Information
Patent Citations
Method for hydrothermal synthesis of oil product hydrogenation catalyst
CN105363461A
Ultra-deep hydrodesulfuration catalyst carrier for poor diesel fuel as well as preparation method and application of catalyst carrier
CN106694025A
Hydro-upgrading catalyst, and preparation method and application thereof
CN107442161A
Preparation method of hydrogenation catalyst
CN108620082A
Hydrodesulfurization catalyst as well as preparation method and application thereof
CN114522694A